Differences in myocardial strain between pectus excavatum patients and healthy subjects assessed by cardiac MRI: a pilot study - Lollert, André; Emrich, Tilman; Eichstädt, Jakob; Kampmann, Christoph; Abu-Tair, Tariq; Turial, Salmai; Düber, Christoph; Kreitner, Karl-Friedrich; Staatz, Gundula (European radiology, 2018)
Objectives To evaluate differences in myocardial strain between pectus excavatum (PE) patients and healthy subjects (HS) assessed by cardiac MRI using the feature-tracking algorithm. Methods Cardiac MRI was performed in 14 PE patients and 14 HS (9:5 male to female in each group; age 11–30 years) using a 3T scanner. Post-examination analysis included manual biventricular contouring with volumetry and ejection fraction measurement by two independent radiologists. Dedicated software was used for automated strain assessment. Results In five of the PE patients, the right ventricular ejection fraction was slightly impaired (40–44 %). PE patients had a significantly higher left ventricular longitudinal strain ( P =0.004), mid ( P =0.035) and apical (P=0.001) circumferential strain as well as apical circumferential strain rate ( P =0.001), mid right ventricular circumferential strain ( P =0.008) and strain rate ( P =0.035), and apical right ventricular circumferential strain ( P =0.012) and strain rate ( P =0.044) than HS. The right ventricular longitudinal strain and strain rate did not differ significantly between PE patients and HS. Conclusions Myocardial strain differs significantly between PE patients and HS. Higher myocardial strain in the mid and apical ventricles of PE patients indicates a compensation mechanism to enhance ventricular output against basal sternal compression. Key Points • The right ventricle is frequently affected by the pectus excavatum deformity. • Cardiac MRI revealed differences in myocardial strain in pectus excavatum patients. • Pectus excavatum patients exhibited higher strain in the mid/apical ventricles. • A compensation mechanism to enhance ventricular output against sternal compression is possible.